CARICOM report No. 2 - Jessen, Anneke (IDB-INTAL Buenos AiresAR, 2005)
Assesses recent progress achieved in the three main areas of the integration process viz. economic integration, foreign policy coordination and functional cooperation. Analyzes the determinants of integration in an effort to generate a better understanding of the challenges and prospects of the Caribbean integration process.